DETERMINAN PEMAHAMAN AKUNTANSI MAHASISWA DENGAN SELF REGULATION SEBAGAI VARIABEL MODERASI - Khaeruddin, Faizah (ISAFIR: Islamic Accounting and Finance Review, 2024)
This study aims to analyze determinants of students accounting understanding with self-regulation as a moderating variable in accounting students at Makassar State University. This type of research is a type of quantitative research. The population in this study were accounting students who were registered at the Makassar State University. Determination of research sample based on convenience sampling method. Research data is primary data collected through a questionnaire survey using google form. Data analysis used multiple linear regression analysis to determine the effect of intellectual ability, social ability, and spiritual intelligence on the understanding of accounting courses. Moderating regression analysis with Interaction Approach Test to determine the effect of self-regulation in moderating intellectual ability, social ability, and spiritual intelligence on the understanding of accounting courses. The results of this study indicate that spiritual intelligence has a significant positive effect on accounting understanding. Meanwhile, intellectual ability and social ability have no significant effect on accounting understanding. The self-regulation variable does not become a moderator variable on the intellectual ability variable and the social ability variable on accounting understanding. The self-regulation variable becomes a moderator variable on the intellectual ability variable on accounting understanding.